IκK-16 decreases miRNA-155 expression and attenuates the human monocyte inflammatory response - Galbraith, Norman James (PLoS One, 2017)
Excessive inflammatory responses in the surgical patient may result in cellular hypo-responsiveness, which is associated with an increased risk of secondary infection and death. microRNAs (miRNAs), such as miR-155, are powerful regulators of inflammatory signalling pathways including nuclear factor κB (NFκB). Our objective was to determine the effect of IκK-16, a selective blocker of inhibitor of kappa-B kinase (IκK), on miRNA expression and the monocyte inflammatory response. In a model of endotoxin tolerance using primary human monocytes, impaired monocytes had decreased p65 expression with suppressed TNF-α and IL-10 production (P < 0.05). miR-155 and miR-138 levels were significantly upregulated at 17 h in the impaired monocyte (P < 0.05). Notably, IκK-16 decreased miR-155 expression with a corresponding dose-dependent decrease in TNF-α and IL-10 production (P < 0.05), and impaired monocyte function was associated with increased miR-155 and miR-138 expression. In the context of IκK-16 inhibition, miR-155 mimics increased TNF-α production, while miR-155 antagomirs decreased both TNF-α and IL-10 production. These data demonstrate that IκK-16 treatment attenuates the monocyte inflammatory response, which may occur through a miR-155-mediated mechanism, and that IκK-16 is a promising approach to limit the magnitude of an excessive innate inflammatory response to LPS.